ncRNA BC1 influences translation in the oocyte - Aleshkina, D; Iyyappan, R; Lin, Ch J; Masek, T; Pospisek, M; Susor, A (RNA biology, 2021)
Regulation of translation is essential for the diverse biological processes involved in development. Particularly, mammalian oocyte development requires the precisely controlled translation of maternal transcripts to coordinate meiotic and early embryo progression while transcription is silent. It has been recently reported that key components of mRNA translation control are short and long noncoding RNAs (ncRNAs). We found that the ncRNABrain cytoplasmic 1 (BC1) has a role in the fully grown germinal vesicle (GV) mouse oocyte, where is highly expressed in the cytoplasm associated with polysomes. Overexpression of BC1 in GV oocyte leads to a minute decrease in global translation with a significant reduction of specific mRNA translation via interaction with the Fragile X Mental Retardation Protein (FMRP). BC1 performs a repressive role in translation only in the GV stage oocyte without forming FMRP or Poly(A) granules. In conclusion, BC1 acts as the translational repressor of specific mRNAs in the GV stage via its binding to a subset of mRNAs and physical interaction with FMRP. The results reported herein contribute to the understanding of the molecular mechanisms of developmental events connected with maternal mRNA translation.
Keywords: nekódující RNA; embryo; myši; oocyty; Protein Biosynthesis; cytoplazma; translation; Mice, Inbred ICR; Polyribosomes; Mice; Animals; Non-coding RNA; RNA malá cytoplazmatická; oocyte; zvířata; myši inbrední ICR; oogeneze; proteosyntéza; Oogenesis; polyribozomy; Cytoplasm; development; ženské pohlaví; Female; RNA, Untranslated; RNA, Small Cytoplasmic; Oocytes